A Review of Failures and Malfunctions in Hydraulic Sandblasting Perforation Guns - Zhengxuan Luan; Liguo Zhong; Wenqi Feng; Jixiang Li; Zijun Gao; Jiaxin Li (Applied Sciences)
Hydraulic sandblasting perforation guns play a critical role in well completion and productivity enhancement operations in oil and gas wells, as their performance and service life directly affect perforation efficiency, reservoir integrity, and downhole operational safety. Drawing on a comprehensive review of the existing literature, this paper systematically summarizes recent research progress on surface erosion, high-pressure leakage, and vibration-induced fatigue in perforation guns. Regarding erosion wear, we discuss the mechanisms and preventive strategies influenced by abrasive particle flow characteristics, material selection, and coating applications. In the field of high-pressure leakage, we analyze the key factors of seal failure, structural deformation, and material degradation that contribute to leakage formation, and we provide improvement measures involving seal structure optimization, enhanced material properties, and real-time monitoring technologies. Concerning vibration and fatigue, we elucidate the multi-factor coupling mechanisms of failure—encompassing fluid–solid interactions, cavitation impacts, and stress concentration—and outline mitigation strategies through structural redesign, material reinforcement, and fluid dynamic control. Furthermore, the paper anticipates the future trends of intelligent fault diagnosis and predictive maintenance, including multi-sensor data fusion, AI-driven predictive models, and digital twin technologies. Overall, the integrated application of precision design, dynamic optimization, and intelligent control across the entire service life of perforation guns is poised to guide forthcoming research and engineering practices, driving hydraulic sandblasting perforation technology toward greater efficiency, reliability, and intelligence.